Postpartum Women with Urinary Incontinence and Low Back Pain - Azra–A-Ghani, Saima, Ibrahim Shah, Siraj, Sami Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Many women have urinary Incontinence after giving birth. Approximately 36%-44% of postpartum women have urine incontinence symptoms (UI). Incontinence in the postpartum period is often caused by damage to the urethra, the bladder, the nerves that control bladder function, malfunction in the pelvic floor muscles, or all four. Vesical denervation likely causes UI in women who have had a cesarean section by making the detrusor muscle unstable. F.Factors, Surgical Vaginal Birth, and Prenatal Bladder Neck movement owing to dysfunctional Pelvic Floor Muscles (PFM) and weakened Connective Tissue are further risk factors for the development of UI. Joint laxity, weakening of Connective Tissue, Loosened Ligaments and Stretched Abdominal Muscles from the growing uterus all contribute to the typical occurrence of lower back pain (LBP) in women after childbirth. It has been shown that postpartum women who experience low back pain and UI often do so together. Objective: This study aims to determine whether or not Urine Incontinence and Low Back Pain are related in Postpartum Women. Methodology: the study was conducted in Department of Urology at Lady Reading Hospital (LRH) Quota sampling was employed for this analysis. One group consisted of women with low back discomfort after delivery, whereas the other did not. In order to investigate the correlation between UI severity and LBP, participants were given UI questionnaires. Self-administered questionnaires were made available to respondents in English. Because some participants could not read the questionnaires, we had to collect the information from them verbally. Results: Fisher’s exact test was used to look at the distribution of ICIQ-UI scores; the p-value was > 0.05 therefore the null hypothesis was not rejected. This meant that there was no correlation between urinary Incontinence and Lower back pain in women postpartum. Conclusion: This Study concludes disproving the hypothesis that UI and postpartum women experiencing low back discomfort. Keywords: Urinary Incontinence UI), Low Back Pain (LBP), Post Partum period. Pelvic Floor Disorders,